The development of digital teaching materials using Macromedia flash for Junior High School class VII - Fanzeka, Daniel; Rusli, R.; Hastuty, H.; Nasrullah, N. (ARRUS Journal of Mathematics and Applied Science, 2021)
This research aims to develop and produce digital teaching materials products using Macromedia flash application that are valid, practical and effective. This research method refers to a 4D development, and disseminate. Research instruments in the form of validation sheets by material expert and media expert to measure validity; questionnaires of learners; responses to measure practicality; and test of learning outcomes to measure effectiveness. The trial of teaching materials was conducted to class VII learners at SMPN 6 Makassar. The result showed that digital teaching materials developed using Macromedia flash applications in class VII junior high school comparison materials had valid criteria with validity score of 3.70 for the material and 3.50 for media, practically score of 3.60 for small groups and 3.51 for large groups, and effective with an effectiveness score of 90% for small groups and 86%.